Adakitic Paracale Granodiorite in southeastern Luzon, Philippines: A peek at a Proto-Philippine Sea Plate-related magmatic arc - Yumul, Graciano P, Jr (Archīum Ateneo, 2020)
This paper describes the geochemistry, petrogenesis and tectonic setting of a silicic pluton, the Paracale Granodiorite (PG), intruded into an ophiolitic suite in southeastern Luzon island, Philippines. Whole rock chemistry suggests that the PG samples are calc-alkaline and are characterized by light rare earth element (LREE)-enrichment and relatively weak heavy rare earth element (HREE)-depletion. They also show depletion in Nb, Ta, Zr and Ti and positive anomalies in K, Pb and Sr when normalized with the Primordial Mantle and normal-mid-ocean ridge basalt (N-MORB). The PG biotite mineral chemistry shows an affinity to calc-alkaline trends based on the FeOtot versus Al2O3, whereas in the MgO-Al2O3 plot, they exhibit transitional calc-alkaline to peraluminous characteristics. These information, along with a temperature >600 °C based on biotite chemistry, and hydrous setting for the generation of the PG suggest generation in a subduction-related setting. When plotted in the Y versus Sr/Y and YbN versus (La/Yb)N, the PG samples exhibit adakitic signature. Partial melting, fluid addition and sediment participation are discerned from the geochemistry. Melting, assimilation, storage and homogenization (MASH) with limited fractionation are the dominant mechanisms of formation. The PG could represent a Late Cretaceous to Paleogene magmatic arc generated during the subduction of the proto-Philippine Sea Plate.